The online data pre-processing for CBM-TOF - Xiang, C. Z.; Herrmann, Norbert; Deppner, Ingo Martin; Loizeau, Pierre-Alain; Zhang, Yapeng (Journal of Instrumentation, 2013)
The Compressed Baryonic Matter (CBM) experiment will operate a free streaming data acquisition system. In order to optimize the data bandwidth and to achieve high performance, a data pre-processing is designed in the readout chain for the CBM-TOF detector. In this paper, we present the design of this module, results of its simulations and preliminary in-beam results which obtained with a test setup on the proton beam at the COSY accelerator in Jülich, Germany.